Preparing project reports: some guidelines - Singla, M.L. (2000)
Project report is a part of curriculum in all the business schools. A project report, though rich in content, may be very poor, if it is not well organised and presented in a appropriate way. In this paper, the author has dealt with in detail various guidelines, which if followed, would make a project report a fine piece of work. Thus this paper would act as a training manual to those interested to get an insight about preparing the project reports. - Reproduced
Keywords: Project design